The influence of various recovery modalities on performance tasks in basketball players - Myles, J. R.; Lee, C. M.; Kern, M. (International Journal of Applied Exercise Physiology, 2017)
This study aimed to investigate the effectiveness of three recovery strategies during high-intensity intermittent exercise. Nine male basketball players (age, 23.11 ± 2.8 years; height, 1.83 ± 0.1 m; body mass, 81.87 ± 11.2 kg) completed a series of 3 randomized trials. Each trial consisted of a basketball exercise simulation test (BEST), a series of performance tests, one of three recovery modalities, and a subsequent series of performance tests. The performance tests included the agility t-test, a maximal vertical jump test, and a line drill test. Furthermore, participants were also asked to rate their perception of fatigue using a 0-10 scale prior to each series of tests. The three recovery conditions lasted 8 minutes each and were active recovery (AR; cycling at 12.8 kg·m/min per kg bodyweight), sitting in a chair (SIT), or standing with minimal movement (STAND). Prior to participation, players` recovery preferences and habits were recorded to examine possible psychological effects. Results indicated that perceived fatigue was greater following AR compared to SIT and STAND. The agility score was worse following the AR condition, whereas it was unchanged following SIT and STAND. Line drill performance was also worse following the AR condition when compared to SIT and STAND. Psychological variables were not correlated to any performance measures. These findings suggest that active recovery, at the intensity used in this investigation, may limit restoration of performance during intermittent activities such as basketball.